Trajnostna potrošnja - Burja, Alenka (Trajnost, 2025)
The world is changing rapidly and radically. In the first place is probably the looming climate change; uncontrolled temperatures, extreme weather events, melting of permafrost and ice, deforestation. Then there is the lack of food, low-quality food, pesticide residues in the soil, animals and people, the same is true with microplastics. Huge amounts of waste will soon overwhelm us. In some places, there is almost no clean drinking water left, the seas are irreversibly polluted. More than 100,000 people die every year in Europe due to air pollution from traffic. Biodiversity is more than depleted, invasive species are spreading. The population is aging, new diseases are appearing, and there are more and more obese people. And there are more and more rich people on one side, and poor people on the other side; the richest 1 percent of people in the world own 59 percent of all the world‘s wealth. There are currently dozens of war hotspots in the world. It shows that people have forgotten what balanced, sustainable development is. And that we play an important, even the most important, role in all these developments - both in society and in the environment and economy. As individuals, as consumers, as households. What kind of world do we live in and in what direction is our development going depends especially on our lifestyle, the way of life, our daily decisions. Sustainable consumption is one of the appropriate ways forward. Preservation of the planet is our only solution.
Keywords: ključni sektorji potrošnje; krožno gospodarstvo; odtis potrošnje; trajnostna potrošnja